Endocrinology in obstetrics and gynecology - Khadilkar, Suvarna (The Health Sciences Publisher, 2015)
The book thoroughly discusses all the endocrine problems we face in day-to-day practice as well as some rare endocrine diseases. The book covers puberty disorders, contrasexual disorders, menstrual disorders, amenorrhea, infertility, hormonal contraception, endocrine problems in pregnancy, menopause, osteoporosis, lifestyle diseases, hormones and cancer, last but not least, it gives an overview of ovarian transplant as well